Heart failure and preserved left ventricular function: long term clinical outcome. - Israel Gotsman (Public Library of Science (PLoS), 2012)
Background Patients with heart failure (HF) have a poor prognosis. The proportion of patients with HF and preserved left ventricular function (LVF) is increasing. Long term prognosis of HF with preserved LVF may not be so benign. Objectives To evaluate the long term clinical outcome of patients with HF and preserved LVF and predictors of outcome. Methods We prospectively evaluated 309 patients hospitalized with a definite clinical diagnosis of HF. Patients were followed for a mean of 6.5 years for clinical outcome. Results More than a third (36%) of the patients had preserved systolic LVF based on echocardiography. The long term survival rate in this group was poor and not significantly different from patients with reduced LVF (28% vs 23% respectively, P=0.2). The adjusted survival rate by Cox regression analysis was also not significantly different (hazard ratio 1.16, 95% confidence interval 0.87-1.55, P=0.31). The event free survival from death or heart failure re-hospitalization was also low in both groups and not significantly different between patients with preserved vs. reduced LVF (12% vs. 10% respectively, P=0.2). Predictors of mortality in patients with preserved LVF were age, functional capacity and serum urea levels. Conclusions The long term clinical outcome of patients with heart failure and preserved LVF is poor and not significantly different from patients with reduced LVF.